Er(3+) doped phosphoniobate glasses and planar waveguides: structural and optical properties - Barbosa, A. J. [UNESP]; Dias Filho, F. A. [UNESP]; Maia, L. J. Q. [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Goncalves, R. R. (Iop Publishing Ltd, 2008)
Phosphoniobate glasses with composition (mol%) (100-x) NaPO(3)-xNb(2)O(5) ( x varying from 11 to 33) were prepared and characterized by means of thermal analysis, Fourier transform infrared spectroscopy, Raman scattering and (31)P nuclear magnetic resonance. The addition of Nb(2)O(5) to the polyphosphate base glass leads to depolymerization of the metaphosphate structure. Different colors were observed and assigned as indicating the presence of Nb(4+) ions, as confirmed by electron paramagnetic resonance measurements. The color was observed to depend on the glass composition and melting temperature as well. Er(3+) containing samples were also prepared. Strong emission in the 1550 nm region was observed. The Er(3+4)I(15/2) emission quantum efficiency was observed to be 90% and the quenching concentration was observed to be 1.1 mol%( 1.45 x 10(20) ions cm(-3)). Planar waveguides were prepared by Na(+)-K(+)-Ag(+) ion exchange with Er(3+) containing samples. Optical parameters of the waveguides were measured at 632.8, 543.5 and 1550 nm by the prism coupling technique as a function of the ion exchange time and Ag(+) concentration. The optimized planar waveguides show a diffusion depth of 5.9 mu m and one propagating mode at 1550 nm.